Lucerne da Antinoupolis Scavi della necropoli nord 1965-1966 - SPANU, Marcello (Edizioni dell'Istituto Papirologico «G. Vitelli», 2022)
The volume focuses on the study of 567 lamps, coming from the excavations of the North Necropolis of Antinoupolis carried out in the years 1965 and 1966 by the Papyrological Institute "G. Vitelli", Florence. The examined lamps (mostly in an excellent state of conservation) constitute one of the most numerous collections of this ceramic class and are placed between the 5th and 7th century AD. The specimens analyzed are mostly locally produced, for which a typology based on shape and motifs is proposed, while the rest are imported (mostly from other centers of Egypt). Although conditioned by the scarcity of data available, the study of this collection therefore constitutes an important basis for the outline of the trades active in Antinoupolis in the pre-Islamic era.